IMPROVEMENT IN QUALITY-OF-LIFE AFTER LAPAROSCOPIC NISSEN FUNDOPLICATION - KAPPAZ,Guilherme Tommasi (2014)
Context Evaluating quality of life after surgery for gastroesophageal reflux is fundamental, since improvement of symptoms is the main goal of treatment. Objective To compare the satisfaction of patients operated for GERD, interviewed at the office, with patients interviewed by telephone. Methods One hundred and seventy-eight patients were submitted to laparoscopic Nissen fundoplication. Ninety patients were found, and 45 agreed to come to the hospital’s office. The other 45 patients were interviewed by telephone. Quality of life was evaluated using three methods: The GERD-HRQL questionnaire, translated to Portuguese; question “If you could choose it today, would you do surgery again?”; and question “If you could classify your symptom improvement between 0 and 10, which grade would you give?” Patients were divided in group A (office interview) and B (telephone interview). Statistical analysis was performed. Results The average GERD-HRQL score in group A was 6.29, while in group B was 14.09(P = 0.002). There was no statistical difference between groups A and B regarding patients choice of doing the surgery again(P = 0.714) and their grade of postoperative symptom improvement (P = 0.642). Conclusion The overall postoperative satisfaction was high. The GERD-HRQL questionnaire might not be suitable for application by telephone in our population, and based on other analyzes, the satisfaction and quality of life of patients interviewed at the office or by telephone was similar.